Mechanistic insight into cooling-rate-driven bubble evolution and interfacial bonding strength in directly bonded Ti–PET materials - Katsuyoshi Kondoh; Nodoka Nishimura; Kazuki Shitara; Shota Kariya; Ke Chen; Abdillah Sani Bin Mohd Najib; Junko Umeda (Journal of Advanced Joining Processes)
This study elucidates the mechanistic relationship between cooling rate and interfacial bubble evolution in direct bonding of commercially pure titanium (Ti) to polyethylene terephthalate (PET). Joints were fabricated via a thermal press-bonding process under two distinct cooling regimes—rapid and slow cooling—and the dynamic behavior of residual gas bubbles was analyzed through in-situ optical observation. Slow cooling was found to markedly reduce both the size and population density of interfacial bubbles, attributed to enhanced gas re-dissolution and diffusion within the softened PET matrix at elevated temperatures. Quantitative image analysis revealed that the bubble area fraction decreased by >50 % under slow cooling conditions. Tensile shear testing showed that joints fabricated under slow cooling exhibited significantly higher bond strength—up to 1.5 times greater than those produced under rapid cooling—highlighting the deleterious role of residual bubbles as interfacial defects. Fractographic observations further indicated that slow cooling altered bubble morphology from network-like, dome-shaped structures to isolated, spherical forms, thereby increasing the effective bonded area and promoting interfacial adhesion. These findings provide critical insight into thermally driven interfacial phenomena in metal–polymer joining and underscore the importance of thermal management strategies for optimizing joint integrity.